2019
DOI: 10.1002/iub.2114
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization Of Alpers encephalopathy associated mutants of human mitochondrial phenylalanyl‐tRNA synthetase

Abstract: Mutations in nucleus‐encoded mitochondrial aminoacyl‐tRNA synthetases (mitaaRSs) lead to defects in mitochondrial translation affecting the expression and function of 13 subunits of the respiratory chain complex leading to diverse pathological conditions. Mutations in the FARS2 gene encoding human mitochondrial phenylalanyl‐tRNA synthetase (HsmitPheRS) have been found to be associated with two different clinical representations, infantile Alpers encephalopathy and spastic paraplegia. Here we have studied three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Mitochondrial phenylalanyl-tRNA synthetase, encoded by the nuclear gene FARS2, catalyzes the recognition and binding of Phe and mt-tRNA Phe in the mitochondria (5). Mutations in the FARS2 gene are associated with central nervous system (CNS) diseases, such as autosomal recessive spastic paraplegia (7), epileptic encephalopathy (8)(9)(10), and infantile mitochondrial Alpers encephalopathy (11)(12)(13). In addition, our group reported that a missense homozygous mutation [c.424 G > T (p.D142Y)] in the FARS2 gene was the underlying cause of hereditary spastic paraplegia in a Chinese family (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial phenylalanyl-tRNA synthetase, encoded by the nuclear gene FARS2, catalyzes the recognition and binding of Phe and mt-tRNA Phe in the mitochondria (5). Mutations in the FARS2 gene are associated with central nervous system (CNS) diseases, such as autosomal recessive spastic paraplegia (7), epileptic encephalopathy (8)(9)(10), and infantile mitochondrial Alpers encephalopathy (11)(12)(13). In addition, our group reported that a missense homozygous mutation [c.424 G > T (p.D142Y)] in the FARS2 gene was the underlying cause of hereditary spastic paraplegia in a Chinese family (7).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our group reported that a missense homozygous mutation [c.424 G > T (p.D142Y)] in the FARS2 gene was the underlying cause of hereditary spastic paraplegia in a Chinese family (7). Because CNS disorders are recognized as the major manifestations of FARS2 gene mutations, previous research into the potential molecular mechanisms involved in the pathogenicity of these mutations has focused on the CNS (7,8,10,(12)(13)(14)(15)(16), and little is known about their effects on the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%